2022
DOI: 10.1159/000526381
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Missense Variant in the N-Terminal Region of ANK3 Gene Is Associated with Developmental Delay, Seizures, Speech Abnormality, and Aggressive Behavior

Abstract: <b><i>Introduction:</i></b> Intellectual disability (ID) is a lifelong disability that affects an individual’s learning capacity and adaptive behavior. Such individuals depend on their families for day-to-day survival and pose a significant challenge to the healthcare system, especially in developing countries. ID is a heterogeneous condition, and genetic studies are essential to unravel the underlying cellular pathway for brain development and functioning. <b><i>Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, human studies suggest that SNPs in this region are associated with reduced expression of ANK3 transcripts in patients with BD and accompanied by altered neuropathology [19][20][21]. A recent study identified a female patient with a novel homozygous missense variant (c.178 T > C; p.Tyr60His) in exon-1b of the ANK3 gene who exhibited seizures and mood disturbance [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, human studies suggest that SNPs in this region are associated with reduced expression of ANK3 transcripts in patients with BD and accompanied by altered neuropathology [19][20][21]. A recent study identified a female patient with a novel homozygous missense variant (c.178 T > C; p.Tyr60His) in exon-1b of the ANK3 gene who exhibited seizures and mood disturbance [22].…”
Section: Introductionmentioning
confidence: 99%